2013
DOI: 10.1002/ebch.1950
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody for reducing the risk of respiratory syncytial virus infection in children

Abstract: Background Respiratory syncytial virus (RSV) is one of the most important viral pathogens causing acute respiratory infections, resulting in about 3.4 million hospitalisations annually in children under five. Palivizumab is the only product approved for prevention of serious RSV disease, as motavizumab is no longer being developed for this condition. The efficacy and safety of palivizumab has been evaluated in randomized controlled trials (RCTs) and a large number of economic evaluations (EEs) have tested its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 93 publications
0
36
1
2
Order By: Relevance
“…in reducing the incidence of serious lower respiratory tract RSV disease in children with chronic lung disease, congenital heart disease or those born preterm. [125] In conclusion, we found the burden of respiratory morbidity being generally high in former preterm infants and aggravated in those with BPD. Influenza virus infection plays a minor role compared with RSV associated respiratory tract infection during infancy and early childhood.…”
Section: Review Articlementioning
confidence: 57%
“…in reducing the incidence of serious lower respiratory tract RSV disease in children with chronic lung disease, congenital heart disease or those born preterm. [125] In conclusion, we found the burden of respiratory morbidity being generally high in former preterm infants and aggravated in those with BPD. Influenza virus infection plays a minor role compared with RSV associated respiratory tract infection during infancy and early childhood.…”
Section: Review Articlementioning
confidence: 57%
“…11,12,16,17 Palivizumab, an RSV-specific monoclonal antibody approved for the prevention of RSV infection, is only partially effective (reducing RSV hospitalization rates only by approximately 60%) 16 and is indicated only for the 3% of the total infant population who are born prematurely or have underlying conditions (chronic lung disease, congenital heart disease, immunodeficiencies, or other severe chronic illnesses). 5,16,[18][19][20] GS-5806 is a novel oral small molecule that inhibits RSV entry at low nanomolar concentrations by blocking viral-envelope fusion with the host-cell membrane (for details see the Supplementary Appendix, available with the full text of this article at NEJM.org). A phase 1 study in humans showed that a single dose of 300 mg and multiple doses of up to 75 mg daily for 7 days were not associated with notable adverse events.…”
mentioning
confidence: 99%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) of the total infant population who are born prematurely or who have underlying conditions (chronic lung disease, congenital heart disease, immunodeficiencies or other severe chronic illnesses) [17]. RSV infection in early childhood is associated with recurrent wheezing later in life [9], and palivizumab treatment in otherwise healthy preterm infants results in a significant reduction in wheezing during the first year of life, even after the end of treatment [9].…”
Section: Palivizumabmentioning
confidence: 99%
“…Palivizumab is the only product approved for the prevention of serious RSV disease [17] and, based on seven studies (all sponsored by the drug manufacturing company) involving 11 096 patients, palivizumab would have a favourable preventive effect in children who are at high risk of acquiring severe RSV infection compared with placebo [17], but due to the high costs of the drug, the question remains whether the drug is cost effective [18].…”
Section: Palivizumabmentioning
confidence: 99%